Digital Literacy Overview: Challenges in Online Physics Learning at New Normal Era - Anastasia Novianti Manalu; Yunita Arifatul Wanda; Hilda V. N Worumboy; Indah Slamet Budiarti (Berkala Ilmiah Pendidikan Fisika, 2021)
This study aimed to determine the extent of the digital literacy contribution to physics learning carried out by students at a university in Jayapura city in Physics Education Study Program at new normal era. The descriptive research approach was used in this study. This study’s population were all students of the Physics Education Study Program divided into 4 groups totaling 96 people. Based on the sampling process from 4 existing groups, purposive sampling was carried out so that the selected ones were students from academic year 2017 with a sample size of 18 people. This research was conducted at a university in Jayapura city in Physics Education Study Program, in September 2020. In this study, data collection techniques were used in the form of a closed questionnaire (structured questionnaire) and interviews to carry data triangulation. The results showed that every aspect of digital literacy has a variation in scores and different interpretations. The three aspects are Use Skill (medium), Critical Understanding (medium), and Communicative Abilities (basic). Students have not been able to communicate and participate actively in online learning during physics classroom because they were only at the stage of uploading content. It concluded that online learning deserves of particular attention when it lasts for the long term. The efforts to elevate the process is urgently needed.